SPECIAL FEATURES OF VIRTUAL PRACTICE INTERACTIVE MEDIA DISCIPLINES FOR DISTANCE LEARNING - Mazur М.П.; Petrovsky, C.C.; Yanovsky М.Л. (Journal of Information Technologies in Education (ITE), 2010)
The features of the development of interactive virtual practical training courses for distance learning are examined in the article. The authors propose their own methods of development tools such disciplines as virtual simulation or video-on labs.